2018
DOI: 10.2147/itt.s125070
|View full text |Cite
|
Sign up to set email alerts
|

Review of checkpoint immunotherapy for the management of non-small cell lung cancer

Abstract: Checkpoint immunotherapy uses highly selective humanized monoclonal antibodies against checkpoint signals such as programmed cell death receptor (PD-1) and programmed cell death ligand (PD-L1). By blocking these receptors and signals, the immune system can be reactivated to fight the tumor. Immunotherapy for advanced non-small cell lung cancer (NSCLC) has resulted in a new paradigm of treatment options resulting in improved survival and response rates and has a less severe yet unique toxicity profile when comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 34 publications
0
38
0
5
Order By: Relevance
“…Nivolumab is a fully human immunoglobulin G4 (kappa) isotype monoclonal antibody that binds programmed cell death protein 1 (PD-1) on activated immune cells and disrupts the engagement of the receptor with its ligands programmed death-ligand 1 (PD-L1: B7-H1/ CD274 and PD-L2: B7-DC/CD273), thereby abrogating inhibitory signals and augmenting the antitumor response of the host [1]. In previous clinical trials, nivolumab has shown activity in several tumor types, including melanoma, renal cell carcinoma, non-small cell lung cancer (NSCLC), Hodgkin lymphoma, and malignant pleural mesothelioma.…”
Section: Introductionmentioning
confidence: 99%
“…Nivolumab is a fully human immunoglobulin G4 (kappa) isotype monoclonal antibody that binds programmed cell death protein 1 (PD-1) on activated immune cells and disrupts the engagement of the receptor with its ligands programmed death-ligand 1 (PD-L1: B7-H1/ CD274 and PD-L2: B7-DC/CD273), thereby abrogating inhibitory signals and augmenting the antitumor response of the host [1]. In previous clinical trials, nivolumab has shown activity in several tumor types, including melanoma, renal cell carcinoma, non-small cell lung cancer (NSCLC), Hodgkin lymphoma, and malignant pleural mesothelioma.…”
Section: Introductionmentioning
confidence: 99%
“…Anti‐tumour immunotherapy with immune check point inhibitors especially targeting PD‐1 receptor or its PD‐L1 has changed the landscape in the treatment of advanced non‐small cell lung cancer (NSCLC) exhibiting improved survival and response rates combined with a less toxic profile . Nivolumab is a human IgG4 monoclonal antibody that inhibits PD‐1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Biospecimens provided by biorepositories have facilitated the development of novel approaches to immunotherapy, which are applicable to a broad range of malignancies, including melanomas, ovarian, gastric, and lung adenocarcinomas, and uterine serous endometrial carcinomas. [18][19][20] The checkpoint protein programmed death-ligand 1 (PD-L1 or B7-H1) has a major role in suppressing the immune system. The immune system is inhibited by the binding of PD-L1 to the program cell death protein 1 (PD-1) on cytotoxic CD8 + T cells; this increases apoptosis and provides an inhibitory signal that decreases the proliferation of antigen-specific T cells.…”
Section: Examples To Illustrate Importance Of Bioresourcesmentioning
confidence: 99%